Heat exposure and productivity in orchards: Implications for climate change research. Issue 6 (2nd November 2017) - Quiller, Grant; Krenz, Jennifer; Ebi, Kristie; Hess, Jeremy J.; Fenske, Richard A.; Sampson, Paul D.; Pan, Mengjie; Spector, June T.
ABSTRACT: Recent studies suggest that heat exposure degrades work productivity, but such studies have not considered individual- and workplace-level factors. Forty-six tree-fruit harvesters (98% Latino/a) from 6 orchards participated in a cross-sectional study in central/eastern Washington in 2015. The association between maximum measured work-shift wet-bulb globe temperature (WBGTmax ) and productivity (total weight of fruit bins collected per time worked) was estimated using linear mixed-effects models, adjusting for relevant confounders. The mean (standard deviation) WBGTmax was 27.9°C (3.6°C) in August and 21.2°C (2.0°C) in September. There was a trend of decreasing productivity with increasing WBGTmax, but this association was not statistically significant. When individual- and workplace-level factors were included in the model, the association approached the null. Not considering individual, work, and economic factors that affect rest and recovery in projections of the effects of climate change could result in overestimates of reductions in future productivity and underestimate risk of heat illness.